The Dietary Flavonoid Rhamnetin Inhibits Both Inflammation and Excitotoxicity During Ethanol Withdrawal in Rat Organotypic Hippocampal Slice Cultures. (18th November 2015) - Lutz, Joseph A.; Carter, Megan; Fields, Logan; Barron, Susan; Littleton, John M.
Abstract : Background: Ethanol (EtOH) causes neurotoxicity via several mechanisms including neuroinflammation (during EtOH exposure), and excitotoxicity (during EtOH withdrawal [EWD]). Alpha7 nicotinic acetylcholine receptor (nAChR) selective agonists have the potential to reduce both. The aim of this study was to evaluate the anti‐inflammatory and neuroprotective potential of rhamnetin, a dietary flavonoid with alpha7 nAChR selective activity, in an in vitro model of EtOH‐induced neurotoxicity. Methods: The anti‐inflammatory and neuroprotective properties of rhamnetin were assessed in neonatal organotypic hippocampal slice cultures undergoing EWD (or not) and challenged with N‐methyl‐D‐aspartate (NMDA) and/or lipopolysaccharide (LPS). Neurotoxicity was determined using propidium iodide uptake, and the inflammatory response was evaluated by measuring the release of tumor necrosis factor (TNF)‐alpha (NO; quantified by ELISA) and nitric oxide (quantified by the Griess reaction) into culture media. Results: As predicted, rhamnetin reduced LPS‐induced release of TNF‐alpha and NO both under control conditions and during EWD. Additionally, rhamnetin had no effect on NMDA‐induced neurotoxicity under control conditions, but significantly reduced NMDA toxicity during EWD. In contrast, rhamnetin had no effect on neurotoxicity induced by NMDA and LPS combined despite reducing TNF‐alpha and NO levels under these conditions. Conclusions: Rhamnetin is anti‐inflammatory and neuroprotective during EWD and therefore has potential value in treating neurotoxicity caused by EtOH.